Extraction, Phytochemical Analysis and Study of TPC and TFC In Extract of Achyranthes ASPERA - Shandilya, Manjusha; Singhai, Akhlesh Kumar (Journal of Neonatal Surgery, 2025)
The current study investigates the extraction, phytochemical screening, and assessment of total phenolic and flavonoid content in different solvent extracts of Achyranthes aspera aerial parts. Various extracts, including chloroform, ethyl acetate, methanolic, and aqueous extracts, were prepared, and their yields were calculated. Phytochemical analysis revealed the presence of important bioactive compounds such as alkaloids, flavonoids, diterpenes, phenols, proteins, saponins, and tannins, with methanolic extract showing the highest yield and the most significant phenolic and flavonoid content. The methanolic extract exhibited the highest total phenolic content (1.63 mg/100 mg) and flavonoid content (1.45 mg/100 mg), suggesting its potent antioxidant activity. The findings support the therapeutic potential of Achyranthes aspera in combating oxidative stress and liver diseases. These results lay the groundwork for further studies on the pharmacological properties of Achyranthes aspera and its bioactive constituents.